BETWEEN AN ETHIC OF CARE AND AN ETHIC OF AUTONOMY: negotiating relational autonomy, disability, and dependency. Issue 3 (4th May 2019) - Davy, Laura
Abstract: In this article I review the contested terrain of relationality, dependency and care within contemporary disability studies and feminist care theory. I begin and end with short personal narratives centring on my relationship with my sister, who has an intellectual disability. These stories are my point of departure in exploring the article's central theme – that the agency and autonomy of individual persons only emerges relationally, through the support and enablement of others. I argue that the concept of relational autonomy, which seeks to reconcile an understanding of our constitutive relationality with a respect for individuality, offers a way of thinking through the tensions between care ethics and disability studies productively. In the concept of relational autonomy that I propose, neither autonomy nor care is privileged, but both are placed in service of the other: autonomy cannot be enabled without care, and care cannot be enabling without respect for autonomy. The article concludes with a discussion of representation and the problem of appropriating the other's voice, an area where the question of the dichotomy between dependency and autonomy is particularly pronounced. Looking at the ways in which voice can be supported and enabled through relational forms of representation, I demonstrate how relational autonomy works as a lived dynamic, highlighting the sorts of caring practices and relationships that foster rather than stifle personal autonomy, and the need for greater support from wider social and political institutions to allow these practices and relationships to flourish.